Blue-light cystoscopy in the evaluation of non-muscle-invasive bladder cancer. (February 2014) - Oude Elferink, Puck; Witjes, J. Alfred
Bladder carcinoma is the most common malignancy of the urinary tract. Two distinct groups can be identified: non-muscle-invasive bladder carcinoma (NMIBC) and muscle-invasive bladder carcinoma. At initial resection about 75–85% of the patients will be diagnosed with NMIBC. This subgroup has a recurrence rate up to 70–80%, and a subsequent chance of disease progression. This means that patients with NMIBC require adequate treatment and thorough follow up. This high recurrence rate also means that apparently current diagnosis and treatment can be improved. It is thought that photodynamic diagnosis, by the use of a photosensitizing drug and blue-light cystoscopy, can improve the detection of tumor and therefore affect outcome for patients with NMIBC. In this paper we will discuss the role of blue-light cystoscopy in NMIBC in different aspects of the disease by reviewing the latest literature.